The socio-economic significance of four phonetic characteristics in North American English - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2011)
This paper uses a least-square regression method that relates per-capita income to four phonetic characteristics (r-dropping, and the so-called father-bother, cot-caught and pin-pen mergers), to study the socio-economic significance of those characteristics in North American English. As a result we find a positive and statistically significant relationship between per-capita income and r-dropping, and between per-capita income and the presence of the cot-caught merger, and a negative and statistically significant relationship between per-capita income and the pin-pen merger. No statistically significant relationship is found, however, between per-capita income and the presence of a father-bother merger or split.
Keywords: 330; statistical regression; phonetic characteristics; per-capita income; North American English